Seasonal variations of biogenic secondary organic aerosol tracers in ambient aerosols from Alaska. (April 2016) - Haque, Md. Mozammel; Kawamura, Kimitaka; Kim, Yongwon
Abstract: We investigated total suspended particles (TSP) collected from central Alaska, USA for molecular compositions of secondary organic aerosol (SOA) derived from the oxidation of biogenic volatile organic compounds (BVOCs). Isoprene-, α -/ β -pinene- and β -caryophyllene-SOA tracers were determined using gas chromatography-mass spectrometry. The concentration ranges of isoprene, α -/ β -pinene and β -caryophyllene oxidation products were 0.02–18.6 ng m −3 (ave. 4.14 ng m −3 ), 0.42–8.24 ng m −3 (2.01 ng m −3 ) and 0.10–9 ng m −3 (1.53 ng m −3 ), respectively. Isoprene-SOA tracers showed higher concentrations in summer (ave. 8.77 ng m −3 ), whereas α -/ β -pinene- and β -caryophyllene-SOA tracers exhibited highest levels in spring (3.55 ng m −3 ) and winter (4.04 ng m −3 ), respectively. β -Caryophyllinic acid and levoglucosan showed a positive correlation, indicating that biomass burning may be a major source for β -caryophyllene. We found that mean contributions of isoprene oxidation products to organic carbon (OC) and water-soluble organic (WSOC) (0.56% and 1.2%, respectively) were higher than those of α -/ β -pinene (0.31% and 0.55%) and β -caryophyllene (0.08% and 0.13%). Using a tracer-based method, we estimated the concentrations of secondary organic carbon (SOC) produced from isoprene, α -/ β -pinene and β -caryophyllene to be 0.66–718 ngC m −3 (ave. 159 ngC m −3 ), 7.4–143 ngC m −3 (35 ngC m −3 ) and 4.5–391 ngC m −3 (66.3 ngC m −3 ), respectively. Based on SOA tracers, this study suggests that isoprene is a more important precursor for the production of biogenic SOA than α -/ β -pinene and β -caryophyllene in subarctic Alaska. Highlights: This study presents distinct seasonal variations of SOA tracers in Alaskan aerosols. BVOCs (isoprene, α -/ β -pinene and β -caryophyllene) significantly contribute to SOC (14.4% of OC). Isoprene is a more important contributor for biogenic SOA than α -/ β -pinene and β -caryophyllene in subarctic Alaska.